Financial Reforms in Algeria: Analyzing the Impact of Organic Finance Law 18-15 on Public Accounting, Foreign Investment, Electronic Services, Local Autonomy, and Fiscal Sustainability - Bensaid, Bakhta; Bensaid, Mohamed (Journal of Finance and Financial Law, 2025)
The purpose of the article. This article examines the impact of Algeria's Organic Finance Law 18-15 on the country’s public financial management, foreign investment environment, electronic financial services, local financial autonomy, and overall fiscal sustainability. The study aims to assess whether the comprehensive reforms introduced by OFL 18-15 have effectively enhanced fiscal transparency, improved accrual accounting adoption, facilitated foreign direct investment liberalization, and strengthened local financial governance amidst Algeria’s economic diversification efforts. Methodology. The methodology combines a doctrinal analysis of legislative texts, comparative assessment with international best practices, and empirical evaluation drawing on official budget data and stakeholder interviews conducted in 2023-2024. This mixed-methods approach enables a multi-faceted understanding of reform implementation dynamics, challenges, and outcomes. Results of the research. Findings reveal that OFL 18-15 has significantly advanced accrual-based accounting and performance budgeting frameworks, fostering greater fiscal discipline and transparency. The removal of restrictive foreign ownership caps in non-strategic sectors spurred a moderate increase in foreign investment flows. Digital financial service regulations have promoted fintech growth and enhanced financial inclusion, though infrastructural and regulatory gaps persist. Meanwhile, local governments have gained legislative fiscal autonomy but remain dependent on central transfers, underscoring governance and capacity constraints. Overall, while progress towards fiscal sustainability remains uneven—with persistent deficits linked to hydrocarbon dependence—the reforms have created a critical foundation for long-term economic resilience. The study concludes that continued capacity building, institutional strengthening, and policy integration are essential to fully realize the transformative potential of Algeria’s financial reforms.